PENGEMBANGAN MODEL PEMBELAJARAN BACA-TULIS PERMULAAN DALAM PERSPEKTIF EMERGENT LITERACY - Muakibatul Hasanah (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to develop a model for the learning of early reading-writing to improvestudents’ reading-writing competencies. The research data were the results of a studyof an early reading-writing curriculum, those of a survey on the implementation of andsuggestions for the learning of early reading-writing at elementary schools, and those ofa tryout of the prototype of a model for the learning of early reading-writing. The studyproduced: (1) a model of a guideline for the learning of early reading-writing dividedinto the essence of early reading-writing and strategies in the learning of early readingwritingin the emergent literacy perspective and (2) a model of an early reading-writingmagazine using the performance standard with language characteristics, contents, andtechniques.